The Influence of Workplace Facilities and Work Environment on Employee Involvement with Self-Efficacy as an Intervening Variable (A Study at PT. Saprotan Utama Semarang) - Nuraziz, Rafif Maulidhan; Dihan, Fereshti Nurdiana (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of workplace facilities and work environment on employee involvement, with self-efficacy serving as a mediating variable, at PT. Saprotan Utama Semarang. The research is grounded in the notion that human resources play a vital role in enhancing organizational performance and competitiveness, where adequate facilities, a supportive work environment, and employees’ confidence in their abilities are key determinants. A quantitative approach was employed, using questionnaires as the data collection instrument, and data were analyzed through Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings are expected to demonstrate that workplace facilities and work environment significantly affect both self-efficacy and involvement, while self-efficacy mediates the relationship between them. Practically, this research offers recommendations for companies to foster higher employee involvement by improving workplace facilities, creating a conducive environment, and strengthening employees’ self-efficacy to achieve optimal productivity.